A three-phase power flow analysis for electrical power distribution system with low voltage profile - Hakim, Lukmanul; Wahidi, Muhamad; Murdika, Umi; Milano, Federico; Kubokawa, Junji; Yorino, Naoto (ICITACEE : 2015 2nd International Conference on Information Technology, Computer, and Electrical Engineering, 2015)
This paper proposes a three-phase power flow software tool based on voltage rectangular coordinates and the full Newton-Raphson method. The proposed method is then implemented using Python scripting language and its mathematical library. Comparison with the well-known software OpenDSS developed by EPRI shows promising results. The proposed formulation, in fact, is able to solve ill-conditioned power flow cases. In particular, when tested on a system with very low voltage profile, the proposed method is able to converge without the need to convert the load to voltage-dependent type load as it happens in OpenDSS.